The influence of sintering temperature on the properties of composites of biologic hydroxyapatite and zirconla - (:unkn) unknown (Trans Tech Publications Ltd, 2005)
Bovine derived hydroxyapatite was doped with partially stabilized zircònia with 3, mol% yttria. The influence of sintering temperature and the amount of the incorporated zirconia on densification, mechanical properties, crystalline structure and microstructure was investigated. The results indicate that the produced materials exhibit poorer mechanical properties than the relevant composite materials of enamel derived hydroxyapatite. This difference can be attributed to F, since F-content in bone is much higher than in enamel. Hence, in the light of the prospective use of the investigated materials in biomedicine, bovine derived hydroxyapatite doped with zirconia can potentially serve as graft material for load bearing applications if very small amount of F can be incorporated, in order to resemble the composition of enamel derived apatite.
Keywords: Bovine derived hydroxyapatite; Mechanical properties; Microstructure; Zirconia